2020
DOI: 10.1002/smll.202003543
|View full text |Cite
|
Sign up to set email alerts
|

A Biomimetic Polymer Magnetic Nanocarrier Polarizing Tumor‐Associated Macrophages for Potentiating Immunotherapy

Abstract: The progress of antitumor immunotherapy is usually limited by tumor‐associated macrophages (TAMs) that account for the highest proportion of immunosuppressive cells in the tumor microenvironment, and the TAMs can also be reversed by modulating the M2‐like phenotype. Herein, a biomimetic polymer magnetic nanocarrier is developed with selectively targeting and polarizing TAMs for potentiating immunotherapy of breast cancer. This nanocarrier PLGA‐ION‐R837 @ M (PIR @ M) is achieved, first, by the fabrication of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 47 publications
(54 reference statements)
2
89
0
Order By: Relevance
“…In vivo, experimental tumors were restricted in their growth by treatment with ferumoxytol and showed an increased number of M1-like infiltrating macrophages in comparison to the untreated tumors (52). Other studies also exploited MNPs for inducing M1 polarization of TAMs, as recently shown with polymeric NPs coated with a membrane of LPS treated macrophage, and encapsulating Fe 3 O 4 NPs and the imiquimod (Toll-like receptor 7 agonist, a strong macrophage activator), which were able to polarize TAMs towards M1 and achieve a concomitant restriction of experimental tumor growth (53). The membrane was prepared by the LPS stimulated macrophages to specifically target TAMs without direct M1 polarization effects that can be verified from the macrophage polarization results of PLGA-ION (PI) and membrane-coated PLGA-ION (PI@M) NPs.…”
Section: Mnps For Enhancing Macrophage Anti-tumor Activitymentioning
confidence: 90%
“…In vivo, experimental tumors were restricted in their growth by treatment with ferumoxytol and showed an increased number of M1-like infiltrating macrophages in comparison to the untreated tumors (52). Other studies also exploited MNPs for inducing M1 polarization of TAMs, as recently shown with polymeric NPs coated with a membrane of LPS treated macrophage, and encapsulating Fe 3 O 4 NPs and the imiquimod (Toll-like receptor 7 agonist, a strong macrophage activator), which were able to polarize TAMs towards M1 and achieve a concomitant restriction of experimental tumor growth (53). The membrane was prepared by the LPS stimulated macrophages to specifically target TAMs without direct M1 polarization effects that can be verified from the macrophage polarization results of PLGA-ION (PI) and membrane-coated PLGA-ION (PI@M) NPs.…”
Section: Mnps For Enhancing Macrophage Anti-tumor Activitymentioning
confidence: 90%
“…The cytocompatibility was assessed by the qualitative analysis of calcein‐pyridine iodide and the quantitative analysis of the Alamar Blue assay. [ 20 ] Green and red fluorescence represented live cells and dead cells, respectively. As shown in Figure S9a,b, Supporting Information, regardless of 4T1 cells or human umbilical vein endothelial cells (HUVECs), it was observed under the Zeiss fluorescence microscope (FM) that the green fluorescence in RPsP with the concentrations from 25 to 400 µg mL −1 was not significantly different from the control group and the red fluorescence was not obvious, suggesting that the micelles almost had no toxicity to 4T1 cells and HUVECs.…”
Section: Resultsmentioning
confidence: 99%
“…Iron oxide NPs coated with biomimetic membranes from LPS-treated macrophages have also been designed and tested for TAM re-education in a murine model of breast cancer [115]. These NPs were decorated with a TLR7 agonist to boost the activation of NF-κB [115]. Other authors have also suggested the use of TLR7 and TLR8 agonists to induce the activation of NF-κB to enhance immunotherapy efficacy and to increase TNF-α and IL-6 secretion [129].…”
Section: Nps To Switch Tam To An Antitumor "M1-like" Phenotypementioning
confidence: 99%
“…The transcription factor NF-κB successfully activated TAM to induce M1 polarization [ 114 ]. Iron oxide NPs coated with biomimetic membranes from LPS-treated macrophages have also been designed and tested for TAM re-education in a murine model of breast cancer [ 115 ]. These NPs were decorated with a TLR7 agonist to boost the activation of NF-κB [ 115 ].…”
Section: Nanoparticles To Target and Treat Tumour-associated Macrophagesmentioning
confidence: 99%